Pharmacokinetics and pharmacodynamics studies of a loading dose of cisatracurium in critically ill patients with respiratory failure - Panusitthikorn P. (2023)
Background: Previous studies reported a slow neuromuscular response with the currently recommended dose of cisatracurium in critically ill patients. Pharmacokinetic and pharmacodynamic studies of cisatracurium in critically ill patients are still limited. To our knowledge, this is the first study performed to better understand the pharmacokinetics (PKs) and pharmacodynamics (PDs) of a loading dose of cisatracurium and to identify factors that affect PK and PD changes in critically ill patients. Methods: A prospective PKs and PDs study was designed. Arterial blood samples of 10 critically ill patients with respiratory failure were collected after administering a loading dose of 0.2 mg/kg of cisatracurium. Plasma cisatracurium and laudanosine concentrations were determined using liquid chromatography-tandem mass spectrometry. The achievement of the desired pharmacodynamic response was evaluated by both 1) clinical assessment and 2) train-of-four monitoring. The PK/PD indices were analyzed for their correlation with patient’characteristics and other factors. Results: The one-compartment model best described the plasma pharmacokinetic parameters of cisatracurium. The volume of distribution at steady state and total clearance were 0.11 ± 0.04 L/kg and 2.74 ± 0.87 ml/minute/kg, respectively. The mean time to train-of-four 0/4 was 6 ± 3.86 minutes. A time to the desired pharmacodynamic response of less than 5 minutes was found in 10% of the patients. A positive correlation was found between cisatracurium concentration and albumin levels and between pharmacokinetics data and patient factors [partial pressure of carbon dioxide and respiratory alkalosis]. Conclusion: The currently recommended loading dose of cisatracurium might not lead to the desired pharmacodynamic response in critically ill patients with respiratory failure. Trial registration: ClinicalTrials.gov, NCT03337373. Registered on 9 November 2017.